Voltammetry of surface-bound species: Proton-coupled electrochemical reduction - Menshykau, D; Batchelor-McAuley, C; Compton, R (2011)
We consider the one electron, one proton and also the two electron, two proton reductions of surface-bound species. Two mechanisms of reaction are considered: stepwise and concerted. The voltammetry is modelled under three regimes of proton transport: infinitely fast (fully buffered solution), infinitely slow (infinitely high surface coverage of electrode) and the intermediate case of a finite rate of diffusional mass transport to electrode surface. The types of voltammograms observed in each case are presented and discussed. © 2010 Elsevier B.V. All rights reserved.